2019
DOI: 10.1002/er.4853
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of highly correlated Co‐based quaternary Heusler alloys for spintronics and thermoelectric applications

Abstract: Summary The half‐metallic character of new quaternary Heusler alloys CoXMnAs (X = Ru, Rh) is established along with their thermoelectric, mechanical, and thermodynamic properties. The optimization of energy suggests that alloys are stable in Y2‐type structure with a ferromagnetic character. The electronic band profile through generalized gradient approximation and modified Becke‐Johnson potential indicates the metallic character of alloys. However, with inclusion of Hubbard potential to generalized gradient ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
(73 reference statements)
2
37
0
Order By: Relevance
“…Thus, in order to achieve high ZT, it requires very low thermal conductivity κ , and large Seebeck coefficient S , and electrical conductivity σ 4 . On comparing the results on S with those reported for CoRuMnAs and CoRhMnAs, we found that the maximum value of S , S max in our systems (lies in the range 26–28 μV/K) is less than that found in CoRuMnAs and CoRhMnAs 36 . However, various methods like carrier doping, nanostructuring, and chemical modification 61‐64 can enhance the TE performance of the materials.…”
Section: Structural Propertiessupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, in order to achieve high ZT, it requires very low thermal conductivity κ , and large Seebeck coefficient S , and electrical conductivity σ 4 . On comparing the results on S with those reported for CoRuMnAs and CoRhMnAs, we found that the maximum value of S , S max in our systems (lies in the range 26–28 μV/K) is less than that found in CoRuMnAs and CoRhMnAs 36 . However, various methods like carrier doping, nanostructuring, and chemical modification 61‐64 can enhance the TE performance of the materials.…”
Section: Structural Propertiessupporting
confidence: 51%
“…For example, CoFeCrGe and CoFeTiGe were shown to exhibit figure of merit ZT value of 0.71 and 0.61, respectively 35 . In addition, a maximum value of thermopower │S│ of 53.44 μV/K (44.3 μV/K) was reported in CoRhMnAs (CoRuMnAs) 36 . Furthermore, Lin et al predicted a large Seebeck coefficient (539.20 μV/K at 300 K) and power factor (PF) (7 × 10 10 mW/mK 2 s at 300 K) in ZnFeTiSi 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of PF, the thermoelectric efficiency was also deduced from the figure of merit (ZT = S 2 σT/κ) 63,64 . The depicted curve in Figure 9 shows that throughout all temperature regions ZT ranges from 0.00112 to 0.942.These values clarify that the Cs 2 NbI 6 can be efficiently used for thermoelectric purposes.…”
Section: Resultsmentioning
confidence: 88%
“…TE effect is designated as the reverse of squander heat into electrical energy that is, thermal‐to‐electric energy by using the Seebeck effect to make a way for sustainable energy technology and to overcome the energy crisis. Those materials, which convert heat energy into electrical energy, were called as TE materials 39,40 …”
Section: Resultsmentioning
confidence: 99%